Peptides and their Metal Complexes in Neurodegenerative Diseases: from Structural Studies to Nanomedicine Prospects - Trapani, Giuseppe; Satriano, Cristina; La Mendola, Diego (Current Medicinal Chemistry, 2018)
Background: The metal ions dyshomeostasis is increasingly recognized to play a crucial role in the development of aging-related neurodegenerative diseases. Metal trafficking in the brain is related to proteins regulating both uptake and efflux of metals in neurons. Different pathways may occur, depending on specific binding features of metallo-protein complexes. In particular, copper, zinc and iron are recognized to influence the biochemistry of proteins involved in neurodegeneration (for instance Aβ and α-synuclein), as well as those playing a crucial role in neuronal development and efficiency (neurotrophins). Nowadays the application of peptide-based drugs is widespread for different pathologies, but the short lifetime in vivo due to proteolysis and other shortcomings still limit their use. Methods: A structured search was performed about the state of the art on: i) peptidomimetic approaches used to obtain peptides mimicking the metal binding activities of proteins involved in neurons survival, ii) peptide-based nanostructures, as promising biomaterials in tissue engineering and substrates for neurites outgrowth and synapses formation. Results: Recent developments on metal-binding peptides and peptide nanostructures for therapeutic application in neurodegenerative diseases are reviewed, showing as metal ions interaction may affect structural and biological properties of different proteins involved in neurodegenerative diseases. Conclusion: This review provides a survey on peptides able to mimic some biofunctional activities of the whole protein, e.g., the binding features to metal ions, thus highlighting their promising potentialities as new, more effective, therapeutics. The integration of such peptides into multifunctional nanoplatforms can be a smart route for the development of biomaterials scaffolds and nanomedicine applications.
Keywords: nanoparticles